PENELANTARAN RUMAH TANGGA ( Kajian Hukum dan Gender ) - Nurbaity Prastyananda (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
This paper examines the neglect of household in the perspective of law and gender. The argument, which was developed in this study is that neglect of household as one form of domestic violence, which legally regulated clearly and firmly in the Law of the Republic of Indonesia Number 23 of 2004 on the Elimination of Domestic Violence. Sociologically, neglect of household, related to the construction of gender in the context of patriarchal society, which results in gender inequality with the victims were women and children.